Efficacy and tolerability of levocabastine and azelastine nasal sprays for the treatment of allergic rhinitis - Ralph Mösges; Joachim Spaeth; Ludger Klimek (Mediators of Inflammation)
Levocabastine and azelastine are currently the only antihistamines available as nasal sprays for the topical therapy of seasonal allergic rhinitis. The present study was undertaken to compare the onset of action, efficacy and tolerability of these two agents in a total of 242 patients with this condition. This was an international, multicentre, open-label, randomized, parallel-group trial with 123 patients treated with levocabastine (0.5 mg/ml, two puffs per nostril twice daily) and 119 with azelastine (1 mg/ml, one puff per nostril twice daily). Onset of action was comparable for the two drugs with over 50% of patients in each group reporting significant symptomatic relief within 30 min of administration of the first dose of study medication. Therapeutic efficacy was also found to be comparable in the two groups with no statistically significant intergroup differences reported for any of the parameters evaluated, although assessments of global therapeutic efficacy revealed a trend favouring levocabastine. Levocabastine appeared to be better tolerated than azelastine (p = 0.06), with the incidence of the most common adverse experiences, application site reactions and taste disturbances, significantly higher on azelastine than with levocabastine (5% versus 1%; p = 0.05 and 5% versus 0%; p = 0.01, respectively). In conclusion, levocabastine nasal spray appears to be at least as effective as, but better tolerated than, azelastine nasal spray for the treatment of seasonal allergic rhinitis.